Neural Bases of Cognitive Impairments in Post-Traumatic Stress Disorders: A Mini-Review of Functional Magnetic Resonance Imaging Findings - Dossi, Gabriele; Delvecchio, Giuseppe; Prunas, Cecilia; Soares, Jair C.; Brambilla, Paolo (Frontiers in Psychiatry, 2020)
Introduction: Post-Traumatic Stress Disorder (PTSD) is often associated with impairments in emotional and cognitive domains. Contrarily to the emotional sphere, neural basis underpinnings cognitive impairments are still not well known. Methods: We performed a bibliographic search on PUBMED of all the studies investigating the cognitive impairments in PTSD individuals. We considered only studies that applied cognitive tasks using functional Magnetic Resonance Imaging technique. The inclusion criteria were met by nine studies. Results: Overall, PTSD individuals reported significant impairments in the dorsolateral prefrontal cortex (dorsolateral PFC), anterior cingulate cortex (ACC), inferior frontal gyrus (IFG), insula, inferior temporal cortex, supplement motor area (SMA) and Default Mode Network (DMN). Besides, abnormal activity was reported in subcortical structures (e.g. hippocampus, amygdala, thalamus) and in the cerebellum. Limitations: Cognitive functioning was assessed using different cognitive tasks. Potential confounding factors such as age, sex, symptoms intensity, comorbidities and medications might have influenced the results. Conclusion: So far, the evidence reported that PTSD is not only characterized by emotional impairments but also by specific cognitive disturbances, suggesting Top-Down cognitive deficits in the modulation of external or internal stimuli response. Still, further studies are needed in order to better assess the role of cognitive impairment in PTSD and to develop more targeted therapeutic approaches.